Tillfrisknande och användning av hästar med fång - Liman, Jenny (SLU/Dept. of Anatomy and Histology, 2004)
Laminitis has crippled horses through times and many cures have been used to treat it. Since the mechanism of the disease is yet not fully understood, treatments are only ways to alleviate the pain and at best, slow down the pathological process enough to make time for improvement. This paper is a retrospective study of 71 horses treated by a protocol at Hästsjukhuset Strömsholm. The protocol implies three visits at zero, five and fifteen weeks. At each the horse is evaluated and treated by a veterinarian. Lateromedial x-rays are taken and the farrier performs a dorsal hoof wall resection when appropriate. Resection of the dorsal hoof wall is a technique used with favorable results in several countries (Peremans et al 1991, Eustace & Caldwell 1989). It has however not been used in Sweden to a greater extent. Between the first two visits the horse is kept in strict confinement. If necessary the horse is hospitalized and analgesics are used whenever called for. The horses included were declared sound at least six months prior a telephone interview was conducted. During the interview notes were taken on how the convalescence work had proceeded and whether the horse had been able to return to its previous workload. Of the 71 animals 39 had recovered completely. 47% of the ponies regained full soundness and so did 75% of the horses. Significance for prognosis was tested with a binary regression laminitis, cause, number of feet involved, body condition, radiographic findings and two types of clinical scoring. Significance was proven for age insofar as the outcome was worse the older the horse. Distribution according to sex was even among the patients, but the maresran a higher risk of non-recovery. Horses and ponies in good body condition were well represented among the patients. They regained full soundness to a greater extent than animals in normal body condition. No statistical significance could be proven for the clinical evaluation systems. A certain misinterpretation of the clinical notes could have happened in the adaptation, but this probably illustrates the owner's big part in the outcome. Motivation, patience and economical possibilities seem to matter as much as the clinical picture. Horses with a previous history of laminitis do not recover to a lesser extent, but are retired or put down more frequently.